Factors influencing pregnancy planning of multi-ethnic Asian women with diabetes: a qualitative study - Ismail, Irmi Zarina; Chirk, Jenn Ng; Lee, Ping Yein; Hussein, Norita (Public Library of Science, 2020)
Introduction: Pregnancy planning varies among women with diabetes. Observing that the literature examining the factors affecting diabetic women’s pregnancy intentions in multi-ethnic Asian populations is limited, we sought to explore these factors to give a better perspective on these women’s pregnancy planning. Methods: This qualitative study used individual in-depth interviews to capture the views and experiences of non-pregnant diabetic women of reproductive age in four public health clinics in a southwestern state of peninsular Malaysia from May 2016 to February 2017. The participants were purposively sampled according to ethnicity and were interviewed using a semi-structured topic guide. Interviews were audio-recorded, and transcripts were analysed using thematic analysis. Results: From the 33 interviews that were analysed, four important factors influencing participants’ decisions regarding pregnancy planning were identified. Participants’ perception of poor pregnancy outcomes due to advanced age and medical condition was found to have an impact. However, despite these fears and negative relationships with doctors, personal, family and cultural influences supported by religious ‘up to God’ beliefs took centre stage in the pregnancy intention of some participants. Participants demonstrated a variety of understandings of pregnancy planning. They outlined some activities for pregnancy preparation, although many also reported limited engagement with pre-pregnancy care. Conclusions: This study emphasised the known dilemma experienced by diabetic women considering their desire for an ideal family structure against their perceived pregnancy risks, heterogeneous religious beliefs and the impact of cultural demands on pregnancy intention. This study urges healthcare providers to increase their engagement with the women in pregnancy planning in a more personalised approach.